Urgency of applying the concept of warranty of habitability in house lease agreements in Indonesia - Adia Misqa Imtiyaz; Gratianus Prikasetya Putra (The International Journal of Politics and Sociology Research, 2023)
Adequate housing as a place to live is a human right protected under the Human Rights Act. Shelter is not limited to property rights but also rental housing. Decent housing arrangements are then mentioned in the Housing and Settlement Area Law, namely building safety requirements, minimum building area adequacy, and occupant health. If the freehold housing does not meet the livable criteria, the government's solution is to overcome it with financial assistance. Furthermore, to this day, there is no regulation forcing homeowners who rent out their dwellings to meet the standards of livability. In this case, in order to guarantee the quality of life of tenants, the lease agreement needs to follow the provisions of the warranty of habitability from the United States. This legal research uses normative legal research methods, with a statutory approach and conceptual approach. The criteria for warranty of habitability in the United States vary from the regulation of each state. If the warranty of habitability is not fulfilled and if afterwards the tenant's constructive notice is ignored by the landlord, the tenant can file a case with the respective state court, with the final result of abatement (reduction of rent) or even waiver of rent. If a landlord in Indonesia wants to rent out his/her dwelling, it is necessary to regulate this kind of coercive warranty of habitability and the lease agreement in Indonesia is no longer entirely private.